Inverse expression of estrogen receptor alpha and apolipoprotein B in coronary intimal hyperplasia of surgically repaired congenital heart disease: A pre-atherosclerotic condition? - Castilla Lozano, Maria del Rocio (2014)
Congenital heart diseases (CHD) or the process of their repair leads to an increased risk for adult cardiovascular disease compared with the general population. The proliferation of intimal smooth muscle cells (SMCs), which causes intimal thickenings prior to any evidence of visible lipid deposition, was proposed to be the initial lesion of coronary atherosclerosis. The increasing trend to consider intimal thickenings as possible pre-atherosclerotic lesions is based on the distribution of intimal hyperplasia in children and the localization of characteristic atherosclerotic lesions observed in adult humans. Early coronary artery lesions may range from focal areas with mild myointimal thickenings in prenatal life to early soft plaques in infants, which may also present as intermingled lesions with components of both categories, more frequently observed with increasing age. Also,we proposed that TGF-β1 expressionmight be considered another possible predisposing factor to develop atherosclerotic coronary artery disease in CHD patients. On the other hand, estrogen receptor-α (ERα) appears to be responsible for the protective effects of estrogens against atherosclerotic vascular disease. The aim of this paper was to analyze the immunohistochemical expression of ERα, TGF-β1 and apolipoprotein B in coronary intimal hyperplasia in children with CHD and the possible increased risk for the development pre-atherosclerotic lesions.